New perspectives on the ligands and function of the killer cell immunoglobulin-like receptor KIR3DL2 in health and disease - Shaw, Jacqueline; Kollnberger, Simon (Frontiers in Immunology, 2012)
KIR3DL2/CD158k/p140 is a 3 domain killer cell immunoglobulin-like receptor incorporating cytoplasmic ITIM motifs, expressed as a disulphide-bonded dimer. KIR3DL2 is a framework gene within the KIR locus and is highly polymorphic, with 62 allelic variants possibly coding for protein reported. KIR3DL2 binds to HLA-A3 and A11 in a peptide-dependent fashion and to B27 free heavy chain forms. In addition, KIR3DL2 can also function as an innate immune receptor for delivery of CpG DNA to TLR9 in NK cells. The increased levels of expression of KIR3DL2 compared with other KIR expressed by T cell subsets in healthy individuals suggest it may function as a default KIR receptor. KIR3DL2-expressing natural killer cells and IL17 secreting CD4 T cells have been implicated in the pathogenesis of ankylosing spondylitis. Moreover, KIR3DL2 expression delineates circulating and cutaneous lymphoma T cells in Sezary’s syndrome. Here I discuss how the unique molecular attributes of KIR3DL2 impact on its function on NK and T cells and how this may relate to its role in disease.